PROVIDING INPUT FOR STUDENTS IN LANGUAGE LEARNING IN THE POST COVID 19 - Mohammad, Amiruddin; Sa’adiyah Sy, Evha Nazalatus (Premise: Journal of English Education and Applied Linguistics, 2024)
This study aims to explore how teachers create input in language learning. The study facilitates student interaction and sharing of thoughts in English, which serves as beneficial input for language learning. This study is a qualitative research using a descriptive case study approach. The study details teachers' methods to provide input for language acquisition in the post-COVID-19 period. The participants of this study are the students. Observation and interviews are conducted to get the data of providing input in language learning in the new normal. Teachers employed grammar exercises and communicative practice to give input to their pupils. 14 of 44 students (32%) indicated that grammar exercises encourage active participation. Grammar exercises help to improve the language's beauty. In contrast, 30 (68%) of students said they use commutative practices to meet students in input. It implies that it is important for teachers to design the class to focus on meaningful intake in language learning rather than forms.